2016
DOI: 10.1097/dcr.0000000000000562
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Survival of Small-bowel Adenocarcinoma in the United States

Abstract: The prognosis for small-bowel adenocarcinoma is worse than that for colon cancer, and only surgery improves survival. In contrast to colon cancer, a survival benefit from current chemotherapy regimens for small-bowel adenocarcinoma is not seen, suggesting that it may be overused and needs more rigorous study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 21 publications
6
69
1
4
Order By: Relevance
“…With none of the risk factors (as in the present case), a jejunal adenocarcinoma is an even rarer diagnosis. Recently, Young et al [8] have revealed that surgery seems to be the only treatment that improves survival on small bowel adenocarcinoma, and no benefit was seen by adding chemotherapy regimens. Even so, the 5-year survival rate after diagnosis is around 30% [5] .…”
Section: Discussionmentioning
confidence: 99%
“…With none of the risk factors (as in the present case), a jejunal adenocarcinoma is an even rarer diagnosis. Recently, Young et al [8] have revealed that surgery seems to be the only treatment that improves survival on small bowel adenocarcinoma, and no benefit was seen by adding chemotherapy regimens. Even so, the 5-year survival rate after diagnosis is around 30% [5] .…”
Section: Discussionmentioning
confidence: 99%
“…The rarity of small-intestine adenocarcinoma restricts studies of its treatment and prognosis. Moreover, because the small intestine is located near the large intestine, small-intestine adenocarcinoma is generally considered to be similar to colorectal adenocarcinoma, and some of the applied treatments are therefore based on colorectal cancer [6]. There has been far less research into the prognosis of smallintestine adenocarcinoma compared to colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate of patients with colon cancer has decreased owing to improved detection, but the incidence of colon cancer continues to increase 2. Considerable progress in the development of chemotherapy for advanced colon cancer has been observed in the recent decade 3. The epidermal growth factor receptor (EGFR) has been reported as a critical therapeutic target for the treatment of colon cancer 4.…”
Section: Introductionmentioning
confidence: 99%